Inter-relationships among hospitalization measures of psychiatric outcome - Glick, M.; Marsh, A.; Zigler, E. (Journal of Nervous and Mental Disease, 1980)
In a diagnostically heterogeneous sample of 381 first admission male state hospital patients, no consistent correlations appeared among three commonly employed hospitalization measures of outcome. The possibility that psychiatric hospitalization may be a multidimensional criterion is considered and the implications for outcome research are discussed. © 1980 by The Williams & Wilkins Co.
Keywords: Follow-Up Studies; Hospitalization; Human; Length of Stay; Male; Mental Disorders; Models, Theoretical; Patient Readmission; Support, U.S. Gov't, P.H.S.; central nervous system; dept.psy; hospitalization; major clinical study; therapy

Irrational thinking and adjustment to loss of vision - Needham, WE; Ehmer, MN (Journal of visual impairment & blindness, 1980)
Keywords: dept.psy